Pengembangan Aplikasi Konsultasi Alat Kontrasepsi Berbasis Android Sebagai Antisipasi Baby Boom Masa Pandemi Covid-19 - Sukmawati Sukmawati; Sri Andar Puji Astuti; Efri Yandani (Universitas Batanghari Jambi, 2022)
The COVID-19 pandemic caused a drastic decrease in all users of contraceptives, causing the birth rate (baby boom) to increase by 10% during the COVID-19 pandemic. Several factors have contributed to the increasing decline in contraceptive use, including the lack of health facilities with COVID-19 standardized personal protective equipment, causing concern for couples of childbearing age (EFA) thus delaying visits to health facilities to consult or use family planning, and a small number of health facilities in particular. Contraceptive services do not open a practice because they do not have the means to prevent the spread of COVID-19. This study aims to develop an android-based contraceptive consultation application in anticipation of the baby boom during the COVID-19 pandemic. This research on the development of an android-based contraceptive consultation application during the COVID-19 pandemic was developed to facilitate between family planning acceptors and health workers so that the family planning service program continues to run well. This type of research uses quantitative research with a research design using a combined method (combination method) between Research and Development (R&D) and Pre Experiment methods with One group Pre-test and Post-test designs which will be carried out in the working area of Tiumang Health Center, Tiumang District, Dharmasraya Regency, Province West Sumatra. The research instrument used is a questionnaire and informed consent which will be given to respondents at the time of pre-test and post-test with the tool used is an android-based contraceptive consultation application. The steps of this application design model include needs analysis, development design, contraceptive consultation application development, expert validation test, large-small group trial, and android-based contraceptive consulting application product. The results obtained in this study are an application designed and the features needed by EFA in collaboration with experts in the field of information technology (IT). The calculation of application observations carried out by design experts overall reached 84% meaning valid, while content observations / materials in applications carried out by content experts overall reached 80% meaning valid.